2014
DOI: 10.1371/journal.pone.0105593
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping for Seedling and Adult Plant Resistance to Stripe Rust in Synthetic Hexaploid Wheat

Abstract: Use of genetic diversity from related wild and domesticated species has made a significant contribution to improving wheat productivity. Synthetic hexaploid wheats (SHWs) exhibit natural genetic variation for resistance and/or tolerance to biotic and abiotic stresses. Stripe rust caused by (Puccinia striiformis f. sp. tritici; Pst), is an important disease of wheat worldwide. To characterise loci conferring resistance to stripe rust in SHWs, we conducted a genome-wide association study (GWAS) with a panel of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 103 publications
11
144
1
2
Order By: Relevance
“…In the FinchˆEltan RIL population, we have presented two QTL which can be selected via molecular markers to incorporate resistance into wheat varieties. The lack of polymorphisms in the D genome in this population, which is not uncommon [46,47], did not allow us to analyze much of the D genome for resistance loci. Therefore, there may be additional QTL from these cultivars that we were not able to identify with the SNP system used.…”
Section: Discussionmentioning
confidence: 90%
“…In the FinchˆEltan RIL population, we have presented two QTL which can be selected via molecular markers to incorporate resistance into wheat varieties. The lack of polymorphisms in the D genome in this population, which is not uncommon [46,47], did not allow us to analyze much of the D genome for resistance loci. Therefore, there may be additional QTL from these cultivars that we were not able to identify with the SNP system used.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, to avoid potential risk of type II error, a threshold was determined by obtaining p -values within the bottom 0.1 percentile of the distribution. This approach has been used in a few recent GWA studies in wheat (Zegeye et al, 2014; Gao et al, 2016). Based on this approach, a threshold p -value of 0.001 and 0.0001 corresponded to the bottom 0.1 percentile of the distribution for grain yield and yield components and for stripe rust resistance, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…GWAS has several advantages over traditional QTL analysis, such as higher diversity, better utility of the identified QTL across diverse germplasm, and reduced time required for population development [1012]. GWAS has been successfully employed in many plants, such as Arabidopsis [13], maize [10, 14], barley [15, 16], wheat [17, 18], rice [19], oat [20], sorghum [21] and soybean [11, 22]. In cotton, a few genetic studies using GWAS have been reported [2, 4, 23, 24].…”
Section: Introductionmentioning
confidence: 99%